Identification of Syn-Pimara-7,15-Diene Synthase Reveals Functional Clustering of Terpene Synthases Involved in Rice Phytoalexin/Allelochemical Biosynthesis - Wilderman, P. Ross (American Society of Plant Biologists, 2004)
Rice (Oryza sativa) produces momilactone diterpenoids as both phytoalexins and allelochemicals. Accordingly, the committed step in biosynthesis of these natural products is catalyzed by the class I terpene synthase that converts syn-copalyl diphosphate to the corresponding polycyclic hydrocarbon intermediate syn-pimara-7,15-diene. Here, a functional genomics approach was utilized to identify a syn-copalyl diphosphate specific 9β-pimara-7,15-diene synthase (OsDTS2). To our knowledge, this is the first identified terpene synthase with this particular substrate stereoselectivity and, by comparison with the previously described and closely related ent-copalyl diphosphate specific cassa-12,15-diene synthase (OsDTC1), provides a model system for investigating the enzymatic determinants underlying the observed difference in substrate specificity. Further, OsDTS2 mRNA in leaves is up-regulated by conditions that stimulate phytoalexin biosynthesis but is constitutively expressed in roots, where momilactones are constantly synthesized as allelochemicals. Therefore, transcription of OsDTS2 seems to be an important regulatory point for controlling production of these defensive compounds. Finally, the gene identified here as OsDTS2 has previously been mapped at 14.3 cM on chromosome 4. The class II terpene synthase producing syn-copalyl diphosphate from the universal diterpenoid precursor geranylgeranyl diphosphate was also mapped to this same region. These genes catalyze sequential cyclization steps in momilactone biosynthesis and seem to have been evolutionarily coupled by physical linkage and resulting cosegregation. Further, the observed correlation between physical proximity and common metabolic function indicates that other such class I and class II terpene synthase gene clusters may similarly catalyze consecutive reactions in shared biosynthetic pathways.